2008
DOI: 10.1108/01443570810910188
|View full text |Cite
|
Sign up to set email alerts
|

The role of organizational context and infrastructure practices in JIT implementation

Abstract: Purpose -The purpose of this paper is to analyze which factors determine the use of just-in-time (JIT) in companies. More precisely, the paper aims to study the role played by two variables of organizational context (size and age) and three infrastructure practices (advanced manufacturing technologies -AMT, quality management, and work organization). Design/methodology/approach -The hypotheses were tested using data collected from 203 manufacturing plants with at least 20 employees. Data were collected by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 78 publications
(86 reference statements)
1
41
0
9
Order By: Relevance
“…5S can link with total productive maintenance (TPM) (Ahuja & Khamba, 2008) and Japanese management approaches such as TPM, JIT and TQM (Gapp et al, 2008). Generally, the success of 5S implementation depends on organizational characteristics (Sousa &Voss, 2008) as this mentioned in many surveys (Bayo Moriones et al, 2008). Survey of one factory in Iran supports pervious findings in this field and indicates that 5S execution provides better condition for implementation of TPM (Moradi et al, 2011).…”
Section: Review On 5smentioning
confidence: 49%
“…5S can link with total productive maintenance (TPM) (Ahuja & Khamba, 2008) and Japanese management approaches such as TPM, JIT and TQM (Gapp et al, 2008). Generally, the success of 5S implementation depends on organizational characteristics (Sousa &Voss, 2008) as this mentioned in many surveys (Bayo Moriones et al, 2008). Survey of one factory in Iran supports pervious findings in this field and indicates that 5S execution provides better condition for implementation of TPM (Moradi et al, 2011).…”
Section: Review On 5smentioning
confidence: 49%
“…One of the main findings is that Kanban has a significant effect on advanced manufacturing technologies (AMT), basic quality tools and the management of vertical relationships (Bayo-Moriones et al, 2008). Meanwhile, Danese et al (2012) proved that implementing JIT production (using the Kanban system as one of the indicators to measure its implementation) is directly related with enhanced delivery performance.…”
Section: Kanban Systemmentioning
confidence: 99%
“…Fifteen studies in all have been found in the bibliography that use this indicator in the context of JIT (Sakakibara et al, 1997;Lieberman and Demeeter, 1999;Fullerton and McWatters, 2001;Fullerton and McWatters, 2002;Fullerton et al, 2003;Callen et al, 2003;Christiansen et al, 2003;Ahmad et al,2004;Cua et al,2001Cua et al, , 2006Ward and Zhou, 2006;Matsui, 2007;Bayo-Moriones et al, 2008;Inman et al, 2011;Danese et al, 2012).…”
Section: Kanban Systemmentioning
confidence: 99%
“…Tais fatores têm sido discutidos em pesquisas com diferentes orientações metodológicas, como estudos de caso (Lima & Zawislak, 2003;Achanga et al, 2006;Scherrer-Rathje et al, 2009;Piercy & Rich, 2009) e surveys (Cua et al, 2001;White & Prybutok, 2001;Shah & Ward, 2003;Bayo-Moriones et al, 2008;Sim & Rogers, 2008;Freitas et al, 2014).…”
Section: Introductionunclassified